2016
DOI: 10.1111/srt.12335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on breast skin thickness and elasticity: implications for breast support

Abstract: Aging is associated with a significant decline in breast skin thickness and elasticity, which is likely to reduce anatomical breast support. Women might therefore benefit from increased external breast support (i.e. a more supportive bra) with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
7
28
1
Order By: Relevance
“…Nevertheless, as corresponding age dependence plots for these values have quite a large scatter, they cannot be used for supporting or opposing the formulated hypotheses. Data from the skin roughness measurements by the Cutometer are used for arguing and in general are in good agreement with previously reported values (Nedelec et al 2016;Coltman et al 2017).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, as corresponding age dependence plots for these values have quite a large scatter, they cannot be used for supporting or opposing the formulated hypotheses. Data from the skin roughness measurements by the Cutometer are used for arguing and in general are in good agreement with previously reported values (Nedelec et al 2016;Coltman et al 2017).…”
Section: Resultssupporting
confidence: 84%
“…Corresponding skin elasticity parameters (R-parameters) are extracted using the embedded software. Corresponding values measured for all participants were close to the values for the corresponding age groups reported in the literature (Nedelec et al 2016;Coltman et al 2017).…”
Section: Assessment Of the Skin Statesupporting
confidence: 88%
“…Coltman et al reported that breast skin elasticity decreased with age. In our study, age had a moderate negative correlation with breast skin elasticity ( r = –0.353; P < .001) and a weak negative correlation with areolar skin elasticity ( r = –0.237; P = .001).…”
Section: Discussionmentioning
confidence: 99%
“…Many pathologic conditions, including infections, inflammation, primary skin diseases, some systemic diseases, Paget disease, lymphoma, and breast cancer, can affect breast and areolar skin . A limited number of studies in the literature assessed breast skin elasticity, and, to the best of our knowledge, there is no study in the literature that evaluated breast and areolar skin elasticity using SWE.…”
mentioning
confidence: 99%
“…Though mentioned above indices are based on the objective data commonly available or easily obtainable for each person, neither of them was proven totally reliable for determining if the skin of a particular person needs special care and, if so, how intense such care should be. There are also suggestions that using skin analysis methods more sensitive to the intrinsic rather than extrinsic skin features (Guinot et al 2002;Sanders and Newman 2013;Krištić et al 2014;Trojahn et al 2015aTrojahn et al , 2015bTrojahn et al , 2015c; Wang and Dreesen 2018) may be preferable for the express assessment of the perceived age (Gunn et al 2008;Coma et al 2014) together with the methods assessing skin roughness (Edwards et al 2003;Jacobi et al 2004;Masuda et al 2014;Trojahn et al 2015aTrojahn et al , 2015bTrojahn et al , 2015, or skin mechanical properties (Rodrigues 2001;Luebberding et al 2014;Woo et al 2014;Coltman et al 2017). Nevertheless, experimental methods bringing detailed quantifiable information are often demanding complex skin or blood analysis and corresponding equipment with lengthy and expensive measurement procedures.…”
Section: Introductionmentioning
confidence: 99%